Organic Hazes as a Source of Life’s Building Blocks to Warm Little Ponds on the Hadean Earth - Ben K. D. Pearce; Sarah M. Hörst; Joshua A. Sebree; Chao He (The Planetary Science Journal, 2024)
Over 4 billion years ago, Earth is thought to have been a hazy world akin to Saturn’s moon Titan. The organic hazes in the atmosphere at this time could have contained a vast inventory of life’s building blocks and thus may have seeded warm little ponds for life. In this work, we produce organic hazes in the lab in atmospheres with high (5%) and low (0.5%) CH _4 abundances and analyze the solid particles for nucleobases, amino acids, and a few other organics using GC/MS/MS to obtain their concentrations. We also analyze heated (200°C) samples from the high methane organic haze experiment to simulate these particles sitting on an uninhabitable surface. Finally, we use our experimental results and estimates of atmospheric haze production as inputs for a comprehensive numerical pond model to calculate the concentrations of nucleobases from organic hazes in these environments. We find that organic hazes typically provide up to 0.2–6.5 μ M concentrations of nucleobases to warm little ponds for potentially habitable Hadean conditions. However, without seepage, uracil and thymine can reach ∼100 μ M concentrations, which is the present lower experimental limit to react these species to form nucleotides. Heating samples leads to partial or complete decay of biomolecules, suggesting that biomolecule stockpiling on the hot surface is unlikely. The ideal conditions for the delivery of life’s building blocks from organic hazes would be when the Hadean atmosphere is rich in methane, but not so rich as to create an uninhabitable surface.